Cuisenaire rods, an innovative tool for enhancing mathematical Learning - Clemente Panchana , Yuliana María (2025)
Mathematics is fundamental for developing logical thinking, problem-solving, and fostering essential analytical skills. The objective of this research was to evaluate the impact of Cuisenaire Rods as a teaching strategy on the understanding of basic mathematical operations and problem-solving in sixth-grade students of Basic General Education. A quantitative approach was adopted, with a pre-experimental design and observational techniques using a checklist for a sample of 35 students. The results showed that, in the pre-test, students had low performance, 11%–26%, in operations with fractions, percentages, and geometry. After five weeks, an average improvement of 26% was observed, with greater progress in percentages, 11%–57%, and fractions, 26%–51%. Although not all students achieved the expected competencies, the rods proved effective in overcoming difficulties in mathematics. It is recommended to extend the application time and combine them with contextualized exercises to optimize results.